2017
DOI: 10.1080/19768354.2017.1383938
|View full text |Cite
|
Sign up to set email alerts
|

Adding preferred color to a conventional reward method improves the memory of zebrafish in the T-maze behavior model

Abstract: Zebrafish have become a useful model for studying behavior and cognitive functions. Recent studies have shown that zebrafish have natural color preference and the ability to form associative memories with visual perception. It is well known that visual perception enhances memory recall in humans, and we suggest that a similar phenomenon occurs in zebrafish. This study proposes that adding a visual perception component to a conventional reward method would enhance memory recall in zebrafish. We found that zebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 17 publications
5
24
0
Order By: Relevance
“…Similar to our previous findings, a four-day training period was sufficient to allow zebrafish to develop a preference for a particular target compartment, even in the absence of colored cellophane and food during the testing period. Approximately 10 min of hypoxia reversed the effects of training and induced cerebral injury, consistent with our previous results [21,26].…”
Section: Table 1 T-maze Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Similar to our previous findings, a four-day training period was sufficient to allow zebrafish to develop a preference for a particular target compartment, even in the absence of colored cellophane and food during the testing period. Approximately 10 min of hypoxia reversed the effects of training and induced cerebral injury, consistent with our previous results [21,26].…”
Section: Table 1 T-maze Resultssupporting
confidence: 92%
“…Notably, zebrafish have specific color preferences [32]. We previously employed a similar zebrafish behavior model using color preferences in the absence of food rewards [21,26]. Similar to our previous findings, a four-day training period was sufficient to allow zebrafish to develop a preference for a particular target compartment, even in the absence of colored cellophane and food during the testing period.…”
Section: Table 1 T-maze Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…In addition, Kim et al . [40] claimed that there was no color preference between red and green. Since then, the color preference test has been replicated by different groups with their own experimental designs, it is difficult to control the experimental apparatus, the acclimation period and recording time.…”
Section: Discussionmentioning
confidence: 99%
“…This model has recently become regarded as an ideal vertebrate model that has a competitive edge in terms of time and cost for large-scale drug toxicity screening studies [20]. In our previous study, zebra sh were found to be useful in the evaluation of cognitive function including learning and memory [21].…”
Section: Introductionmentioning
confidence: 99%